Graft infusion of adipose‐derived mesenchymal stromal cells to prevent rejection in experimental intestinal transplantation: A feasibility study. Issue 4 (5th February 2021) - Andres, Ane M.; Stringa, Pablo; Talayero, Paloma; Santamaria, Monica; García‐Arranz, Mariano; García Gómez‐Heras, Soledad; Largo‐Aramburu, Carlota; Aras‐Lopez, Rosa M.; Vallejo‐Cremades, Maria Teresa; Guerra Pastrián, Laura; Vega, Luz; Encinas, Jose Luis; et al.
Abstract: Background: Mesenchymal stromal cells (MSC) have been proposed as a promising complement to standard immunosuppression in solid organ transplantation because of their immunomodulatory properties. The present work addresses the role of adipose‐derived MSC (Ad‐MSC) in an experimental model of acute rejection in small bowel transplantation (SBT). Material/Methods: Heterotopic allogeneic SBT was performed. A single dose of 1.5x106 Ad‐MSC was intra‐arterially delivered just before graft reperfusion. Animals were divided into CONTROL (CTRL), CONTROL+Ad‐MSC (CTRL_MSC), tacrolimus (TAC), and TAC+Ad‐MSC (TAC_MSC) groups. Each Ad‐MSC groups was subdivided in autologous and allogeneic third‐party groups. Results: Rejection rate and severity were similar in MSC‐treated and untreated animals. CTRL_MSC animals showed a decrease in macrophages, T‐cell (CD4, CD8, and Foxp3 subsets) and B‐cell counts in the graft compared with CTRL, this decrease was attenuated in TAC_MSC animals. Pro‐ and anti‐inflammatory cytokines and some chemokines and growth factors increased in CTRL_MSC animals, especially in the allogeneic group, whereas milder changes were seen in the TAC groups. Conclusion: Ad‐MSC did not prevent rejection when administered just before reperfusion. However, they showed immunomodulatory effects that could be relevant for a longer‐term outcome. Interference between tacrolimus and the MSC effects should be addressed in further studies.